Fixed-Time Bipartite Containment of Multi-Agent Systems Subject to Disturbance - Li Wang; Jie Wu; Xi-Sheng Zhan; Tao Han; Huaicheng Yan (IEEE Access, 2020)
This paper studies the bipartite containment of multi-agent systems (MASs) subject to the bounded disturbance. Different from the subsistent related works on this topic, the settling time irrespective of initial value can be calculated in advance. Two distributed control algorithms are provided correspondingly for the first-order systems and second-order systems. Based on algebraic theory, properties of the Laplacian matrix and fixed-time stability theory, it shows that fixed-time bipartite containment can be achieved via the presented control law. Simulations are eventually employed to prove the correctness and effectiveness of theoretical results.